2018
DOI: 10.1002/jssc.201800579
|View full text |Cite
|
Sign up to set email alerts
|

Application of a micro plasma collection card for the detection of homocysteine by liquid chromatography with tandem mass spectrometry

Abstract: Generally, it is recommended that blood samples for homocysteine detection should be centrifuged immediately to separate plasma in order to avoid continuous synthesis by blood cells. The use of a micro plasma collection card may improve sample stability and result accuracy by offering automatic and instant plasma separation. We compare a micro plasma collection method with routine wet plasma to explore applications of the dried plasma spots for homocysteine determination by using liquid chromatography with tan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
0
9
0
1
Order By: Relevance
“…[28][29][30][31] This method used one to two drops of blood to produce dried plasma spot (DPS) sample; a fixed accurate volume of plasma was absorbed so that the HCT and blood volume problem may be avoided. 32 This technique in a clinical study has been reported by Li et al who using a filter based DPS card for the quantitation of guanfacine in whole blood. 30 Correction factor was used to calculate estimated plasma concentrations from DPS concentrations for the clinical practice of TDM.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…[28][29][30][31] This method used one to two drops of blood to produce dried plasma spot (DPS) sample; a fixed accurate volume of plasma was absorbed so that the HCT and blood volume problem may be avoided. 32 This technique in a clinical study has been reported by Li et al who using a filter based DPS card for the quantitation of guanfacine in whole blood. 30 Correction factor was used to calculate estimated plasma concentrations from DPS concentrations for the clinical practice of TDM.…”
mentioning
confidence: 90%
“…Recently, a new microsampling method was introduced as an alternative to the DBS approach that could automatically separate blood cells from plasma instantly after blood drawing 28–31 . This method used one to two drops of blood to produce dried plasma spot (DPS) sample; a fixed accurate volume of plasma was absorbed so that the HCT and blood volume problem may be avoided 32 . This technique in a clinical study has been reported by Li et al who using a filter based DPS card for the quantitation of guanfacine in whole blood 30 .…”
Section: Introductionmentioning
confidence: 99%
“…After fingerpricking, the blood drop is deposited on the upper layer, which filters out erythrocytes. The resulting plasma produces calibrated spots on the lower layer [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Classically, liquid whole blood, serum or plasma samples (LPs) (obtained from brachial venipuncture) are employed in the TDM of antipsychotics and concentration reference ranges are available for the interpretation of TDM results [2]. Recently, dried blood (DB), serum, or dried plasma (DP) spot samples have been shown as convenient alternatives to conventional liquid samples for drug measurement [15‐31]. They are easier to collect (even by a self‐directed simple finger pricking), easier to conserve, and to ship abroad because they do not require refrigeration, since analyte degradation is minimized in the absence of water [16].…”
Section: Introductionmentioning
confidence: 99%